2021
DOI: 10.3390/bios11100404
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Study on Brainwave Authentication in a Real-Life Setting: An LSTM-Based Bagging Approach

Abstract: With the advent of the digital age, concern about how to secure authorized access to sensitive data is increasing. Besides traditional authentication methods, there is an interest in biometric traits such as fingerprints, the iris, facial characteristics, and, recently, brainwaves, primarily based on electroencephalography (EEG). Current work on EEG-based authentication focuses on acute recordings in laboratory settings using high-end equipment, typically equipped with 64 channels and operating at a high sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…( 2022 ) Authentication Fingerprint Public dataset: FVC-2004 DB3 Information extraction on minutiae Encryption methods EER: 30% Accuracy: 70% Bhowal et al. ( 2022 ) Authentication Signature Public datasets: SVC 2004 MCYT-100 Physical, frequency-based, and statistical feature extraction A two-tier ensemble approach for classification SVC 2004 Accuracy: 98.43% EER: 2.20 GAR@0.01FAR: 94.50% MCYT-100 Accuracy: 97.87% EER: 2.84 GAR@0.01FAR: 92.90% Libert and Van Hulle ( 2021 ) Authentication EEG Private dataset: 15 subjects STFT for feature extraction LSTM-based network with bootstrap aggregating Performed motor task Accuracy: 92.6% FAR: 2.5% FRR: 5% Imagined motor task Accuracy: 92,5% FAR: 2.6% FRR: 4.9% Combined tasks Accuracy: 93% FAR: 1.9% FRR: 5,1% Kaczmarek et al. ( 2018 ) De-authentication Identification Posture Patterns Private dataset: 30 subjects ML algorithms applied to time series of the force on the sensors True positive rate: 91.0% False positive rate: 0,33% False negative rate: 8.68% Multiple sessions True positive rate: 22%, False positive rate: 5.2%, False negative rate: 72.7% Castiglione et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 2022 ) Authentication Fingerprint Public dataset: FVC-2004 DB3 Information extraction on minutiae Encryption methods EER: 30% Accuracy: 70% Bhowal et al. ( 2022 ) Authentication Signature Public datasets: SVC 2004 MCYT-100 Physical, frequency-based, and statistical feature extraction A two-tier ensemble approach for classification SVC 2004 Accuracy: 98.43% EER: 2.20 GAR@0.01FAR: 94.50% MCYT-100 Accuracy: 97.87% EER: 2.84 GAR@0.01FAR: 92.90% Libert and Van Hulle ( 2021 ) Authentication EEG Private dataset: 15 subjects STFT for feature extraction LSTM-based network with bootstrap aggregating Performed motor task Accuracy: 92.6% FAR: 2.5% FRR: 5% Imagined motor task Accuracy: 92,5% FAR: 2.6% FRR: 4.9% Combined tasks Accuracy: 93% FAR: 1.9% FRR: 5,1% Kaczmarek et al. ( 2018 ) De-authentication Identification Posture Patterns Private dataset: 30 subjects ML algorithms applied to time series of the force on the sensors True positive rate: 91.0% False positive rate: 0,33% False negative rate: 8.68% Multiple sessions True positive rate: 22%, False positive rate: 5.2%, False negative rate: 72.7% Castiglione et al.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, Libert and Van Hulle ( 2021 ) in their work proposed a brainwave authentication system. In particular, the results obtained in this work showed the potential of using this biometric trait to authenticate the identity of a subject in a real-life context (which could also be the work environment) even with only the use of commercial and not particularly accurate hardware (a commercial EEG headset with a dry electrode and chronic recordings).…”
Section: Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, these differences are so distinct that previous works have shown that the identification of a specific subject out-of-many is actually feasible (e.g. [31], [32], [33]). Therefore, modern DLbased BCIs tend to fail to generalize well in unseen subjects due to this type of data distribution shift.…”
Section: Introductionmentioning
confidence: 96%
“…Due to the problem of gradient vanishing and exploding associated with RNN, an advanced architecture of RNN called long-term memory (LSTM) was designed. ,, LSTM has good efficiency in predicting time series because of its unique advantage in solving gradient problems (vanishing and exploding). Also, the term (long-term memory) makes it able to deal with long sequences and predict time series more accurately with more parameters compared to RNN. LSTM depends on the previous input, but in fact, the outputs also depend on the latter inputs, which increases the number of inputs available to the model. Therefore, a new model with an advanced architecture of LSTM has been designed.…”
mentioning
confidence: 99%